DEVELOPMENT LEARNING MEDIA E.A.V ON MATHEMATICAL CONNECTION ABILITY OF JUNIOR HIGH SCHOOL - Akhsanul In'am; Rani Darmayanti; Bhaskoro Prasetyo Adi Maryanto; Retno Wahyu Arian Sah; Kamilia Rahmah (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Technological advances that are overgrowing are also one of the challenges for teachers to use technology as a learning medium. Ethnomathematical animation video as a strategy for linking learning in the real world and mathematical connection skills in solving geometry problems. Therefore, this research aims to create an animated video media based on ethnomathematics on mathematical connection abilities in solving problems in class VIII students. This development study uses the ADDIE metho (Analysis, Design, Develop, Implementation, Evaluation). The results showed that the animated video learning media was adequate, with an overall average score of 3.73 after validation by a Material Expert and an average score of 3.64 after validation by a Media Expert. The responses from the 8th graders were positive (88%) based on the research. Animated video media based on ethnomathematics on mathematical connection abilities can be used as an alternative for teachers in elementary schools to learn geometry material.